2017
DOI: 10.1093/biolre/iox169
|View full text |Cite
|
Sign up to set email alerts
|

Seipin deficiency leads to increased endoplasmic reticulum stress and apoptosis in mammary gland alveolar epithelial cells during lactation†

Abstract: Seipin is an integral endoplasmic reticulum (ER) membrane protein encoded by Berardinelli-Seip congenital lipodystrophy type 2 (BSCL2/Bscl2) gene. Most litters (59%) from Bscl2-/- dams mated with wild type (WT) (Bscl2+/+) males did not survive postnatal day 5 (PND5) and pups (Bscl2+/-) lacked milk in their stomachs. The survived litters had reduced pup survival rate at PND21. It was hypothesized that seipin was critical for lactation. Bscl2 was upregulated and highly detected in the lactation day 1 (LD1) WT ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…In contrast, Liu et al observed ER stress markers positively induced in adipose-specific seipin-knockout mice [ 74 ]. Zowalaty et al also showed ER stress and increased apoptosis in mammary gland alveolar epithelial cells with BSCL2 gene deletion and revealed the importance of seipin for lactation [ 87 ]. BSCL2 knockout was also associated with intensified cerebral ER stress after a transient middle cerebral artery occlusion situation in another study [ 88 ].…”
Section: Seipin Loss-of-functionmentioning
confidence: 99%
“…In contrast, Liu et al observed ER stress markers positively induced in adipose-specific seipin-knockout mice [ 74 ]. Zowalaty et al also showed ER stress and increased apoptosis in mammary gland alveolar epithelial cells with BSCL2 gene deletion and revealed the importance of seipin for lactation [ 87 ]. BSCL2 knockout was also associated with intensified cerebral ER stress after a transient middle cerebral artery occlusion situation in another study [ 88 ].…”
Section: Seipin Loss-of-functionmentioning
confidence: 99%
“…Triglyceride (TG) accounted for more than 98% of milk lipid [ 6 ]. Fatty acids can be rapidly taken up and converted into lipid droplets by the lactating mammary gland [ 7 ]. Non-esterified fatty acid (NEFA) is a source of fatty acids and can increase milk fat synthesis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The middle three sections with the largest areas were selected for area quantification. The total area of each placental section and the areas of labyrinth layer, junctional zone, and decidua, which were outlined manually and quantified using Image J (National Institutes of Health, Bethesda, MD, USA) [35][36][37][38]. The average of each area from three sections in the same placenta was counted as one data point for statistical analysis.…”
Section: Histology and Quantification Of Placental Layersmentioning
confidence: 99%
“…Cross sections (10 μm) of the middle part of frozen placentas from 0 ppm and 40 ppm ZEAtreated groups were collected on the same slides for immunofluorescence. The sections were fixed in 4% paraformaldehyde for 15 min, and blocked with 3% hydrogen peroxide in methanol for 10 min at 25°C, and 10% goat serum in 1x phosphate buffered saline (PBS) for 1 hour at 25°C, incubated with rabbit anti-proliferating cell nuclear antigen (PCNA (D3H8P)1:250, 13110XP, Cell Signaling Technology, Danvers, MA, USA) overnight [35,38,39]. On the second day, the slides were incubated with goat anti-rabbit secondary antibody (Alexa Fluor 288, 1:200, A-11034, ThermoFisher, Rockford, IL, USA).…”
Section: Proliferating Cell Nuclear Antigen (Pcna) Immunofluorescencementioning
confidence: 99%
See 1 more Smart Citation